Do intangible factors enhance sociocultural productivity and economy in world heritage sites? - Martín-Lucas, María; Leal-Solís, Ana; Polo, Ángel Pizarro; Robina Ramírez, Rafael; Moreno-Luna, Libertad (Frontiers in Psychology, 2024)
Measuring the sociocultural productivity of heritage sites remains an ongoing issue for international organizations concerned with the conservation and promotion of traditional sites. The productivity of these locations is not only affected by tangible elements but also by intangible factors, such as the emotions generated by the experiences. For this purpose, 597 employees of hotels in these historical locations who had visited one of the 14 heritage sites in Spain assessed what role emotions play in this contribution. The methodology used was the application of structural equations. Several conclusions have been drawn utilizing the SmartPLS 4 software. The first is that the generation of positive emotions comes exclusively from cultural and historical dynamization and not from technological advances or an eagerness to learn. The second is that both the application of technological advances and cultural dynamization have a direct impact on productivity.